The impact of digital literacy on individual health: a perspective based on fitness exercise - Hao Li; Hao Li; Zihan Yang; Zihan Yang; Jiao Li; Jiao Li (Frontiers in Public Health)
IntroductionRegular fitness exercise is widely recognized as an effective way to improve residents’ health. In the digital economy era, digital literacy, defined as an individual’s capacity to use internet and digital media technologies for information acquisition, screening, and utilization, played a critical role in shaping fitness participation and health outcomes. This study explored the mechanisms by which digital literacy influenced individuals’ engagement in fitness exercise and their subsequent health status.MethodsUsing longitudinal data from the China Family Panel Studies (CFPS) for 2018, 2020, and 2022, we conducted empirical analysis on the effects and pathways through which digital literacy impacted fitness exercise behavior and health. Our methodology included heterogeneous analysis based on individual characteristics and the structural dimensions of digital literacy.ResultsThe findings demonstrated that digital literacy significantly increased individuals’ weekly participation rate and frequency of fitness exercise, although it had no statistically significant effect on the duration of each session. Furthermore, both digital literacy and fitness exercise behavior contributed to improved self-assessed health levels. Heterogeneity analyses revealed that the influence of digital literacy varied across demographic groups, with digital dependence, information acquisition, and digital living environments emerging as key drivers of participation and frequency. The mechanisms linking digital literacy to health improvements included enhanced information access, goal management, social interaction, and online learning.DiscussionTo optimize public health outcomes, policymakers should adopt a people-centered approach, promote the integration of digital technologies with fitness services, and foster environments that support digital literacy development. Addressing disparities in digital literacy within mass fitness initiatives is also crucial for equitable progress.